2021
DOI: 10.1001/jamacardio.2021.2735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Training on Ambulatory Blood Pressure Among Patients With Resistant Hypertension

Abstract: IMPORTANCE Limited evidence suggests exercise reduces blood pressure (BP) in individuals with resistant hypertension, a clinical population with low responsiveness to drug therapy. OBJECTIVE To determine whether an aerobic exercise training intervention reduces ambulatory BP among patients with resistant hypertension. DESIGN, SETTINGS, AND PARTICIPANTS The Exercise Training in the Treatment of Resistant Hypertension (EnRicH) trial is a prospective, 2-center, single-blinded randomized clinical trial performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 16 publications
2
49
1
1
Order By: Relevance
“…Increased physical activity during awake hours of BP measurement could have resulted in transiently higher daytime BP related to physical activity, which was higher in the dietitian telehealth arm than the self-directed arm. In contrast to our findings, Lopes et al reported that a supervised aerobic training program successfully reduced 24-hr systolic BP and daytime BP with no significant effect on nighttime systolic BP (31). A key difference in their trial was that participants were instructed to not exercise during 24-hr ambulatory BP measurements whereas we instructed participants to continue their regular daily routine without any specific restrictions on exercise.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Increased physical activity during awake hours of BP measurement could have resulted in transiently higher daytime BP related to physical activity, which was higher in the dietitian telehealth arm than the self-directed arm. In contrast to our findings, Lopes et al reported that a supervised aerobic training program successfully reduced 24-hr systolic BP and daytime BP with no significant effect on nighttime systolic BP (31). A key difference in their trial was that participants were instructed to not exercise during 24-hr ambulatory BP measurements whereas we instructed participants to continue their regular daily routine without any specific restrictions on exercise.…”
Section: Discussioncontrasting
confidence: 99%
“…The magnitude of the improvements in BP were substantial, similar to a BP medication, and in line with much more resource-intensive feeding studies and lifestyle intervention trials (2, 4, 19, 31). Both the self-directed and the telehealth dietitian arms are scalable interventions that can be easily deployed remotely as the intervention only required internet access and telephone access (no smartphone required).…”
Section: Discussionsupporting
confidence: 75%
“…Ten studies ( N = 380 participants, 51% female , age range 52 to 67 years) were included in the review, of which four ( 15 , 16 , 27 , 28 ) ( N = 58, 50% female) assessed the short-term (≤ 24 h) effects of acute physical exercise and six ( 17 , 18 , 20 , 29 31 ) ( N = 322, 51% female) assessed the mid-term (up to 6 months) effects of exercise training intervention ( Table 1 , Flowchart available as Supplementary Figure 1 ). Participants of two studies ( 19 , 32 ) were enrolled in a larger RCT ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…Available evidence on the effects of exercise intervention in individuals with RH shows promising results, as confirmed by some non-systematic reviews ( 11 14 ). Different trials have reported a beneficial effect of acute ( 15 , 16 ) or regular exercise ( 17 20 ) on office BP or ABP in patients with RH. However, to the best of our knowledge there has been no previous attempts to systematically synthesize the evidence available on the effects of acute or regular exercise on BP measures in patients with RH.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, Santos et al [ 20 ] found significant postexercise hypotension in RH patients who performed low- and moderate-intensity aerobic exercise. Additionally, evidences have demonstrated that aerobic training has a strong capacity to collaborate with changes on BP in RH patients [ 21 , 22 ]. Although some studies have investigated the impacts of aerobic exercise, the effects of resistance exercises on BP and autonomic modulation in this population remain relatively unexplored in the literature.…”
Section: Introductionmentioning
confidence: 99%